Eriodictyonangustifolium extract, but not Eriodictyon californicum extract, reduces human hair greying. (2nd June 2020) - Taguchi, N.; Hata, T.; Kamiya, E.; Homma, T.; Kobayashi, A.; Aoki, H.; Kunisada, T.
Abstract: Objective: Yerba Santa ( Eriodictyon angustifolium and Eriodictyon californicum ) has been used for many years in traditional medicine. However, the effect of Yerba Santa on melanogenesis has not yet been investigated. We aimed to assess the biological effects of Yerba Santa on hair pigmentation. Methods: Yerba Santa extracts were assessed for their cytological effects following X‐ray irradiation treatment and then tested directly for the prevention of human hair greying. Ultra‐performance liquid chromatography (UPLC) was utilized to identify the individual extract components. Results: Eriodictyon angustifolium extract significantly increased melanin synthesis in the melanoma cell line through activation of the WNT/MITF/tyrosinase‐signalling pathway. In contrast, E. californicum had no effect on melanin synthesis. E. angustifolium extract also demonstrated a protective effect against the damage induced by X‐ray irradiation in human keratinocytes. Application of the extracts to subjects who had grey beards demonstrated a reduced number of grey beard hair per year specifically with the E. angustifolium extract. A significant decrease in grey head hair was also observed after application of E. angustifolium extract. Upregulation of gene expression related to melanin production and WNT signalling was observed after the application of E. angustifolium extract. Sterubin was the most abundant flavonoid detected by UPLC in E. angustifolium extract. In addition, sterubin showed the highest difference in terms of quantity, between E. angustifolium and E. californicum extract. Conclusion: Eriodictyon angustifolium extract, which is abundant in sterubin, may be suitable as a potential cosmetic and medical agent for the prevention and improvement of hair greying. Abstract : Eriodictyon angustifolium (Ea) extract, which is abundant in sterubin, can reduce human hair greying. A significant decrease in grey head hair ratio was observed after 24 weeks of Ea extract application. Ea extract may be suitable as a potential cosmetic and medical agent for the prevention and improvement of hair greying. Résumé: OBJECTIF: Yerba Santa ( Eriodictyon angustifolium et Eriodictyon californicum ) est utilisé depuis de nombreuses années en médecine traditionnelle. Cependant, l'effet de Yerba Santa sur la mélanogenèse n'a pas encore été étudié. Notre objectif était d'évaluer les effets biologiques de Yerba Santa sur la pigmentation des cheveux. MÉTHODES: Les extraits de Yerba Santa ont été évalués pour leurs effets cytologiques après un traitement d'irradiation aux rayons X, puis testés directement pour la prévention du grisonnement des cheveux humains. La chromatographie liquide ultra‐performante (UPLC) a été utilisée pour identifier les composants d'extrait individuels. RÉSULTATS: L'extrait d' E. angustifolium a augmenté de manière significative la synthèse de mélanine dans la lignée cellulaire du mélanome par l'activation de la voie de signalisation WNT/MITF/tyrosinase. En revanche, E. californicum n'a eu aucun effet sur la synthèse de mélanine. L'extrait d' E . angustifolium a également démontré un effet protecteur contre les dommages induits par l'irradiation aux rayons X dans les kératinocytes humains. L'application des extraits à des sujets qui avaient une barbe grise a démontré un nombre réduit de poils gris par an spécifiquement avec l'extrait d' E. angustifolium . Une diminution significative des cheveux gris a également été observée après l'application d'extrait d' E. angustifolium . Une régulation à la hausse de l'expression des gènes liée à la production de mélanine et à la signalisation WNT a été observée après l'application d'extrait d' E. angustifolium . La stérubine était le flavonoïde le plus abondant détecté par UPLC dans l'extrait d' E. angustifolium. De plus, la stérubine a montré la plus grande différence en termes de quantité entre E. angustifolium et E. californicum . CONCLUSION: L'extrait d' E. angustifolium, qui est abondant en stérubine, peut convenir comme agent cosmétique et médical potentiel pour la prévention et l'amélioration du grisonnement des cheveux.